Building Readiness for Change: The Impact of High Performance HRM Practices and Transformational Leadership in A Tangerang Private Hospital - Syah, Tantri Yanuar Rahmat; Indriyanti, Winny; Suyitno, Edi; Rojuaniah, Rojuaniah; Astuti, Puji (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study investigates the impact of high-performance Human Resource Management (HRM) practices and transformational leadership on staff preparedness to confront change in a private hospital setting in Tangerang, Indonesia. This study emphasizes the need of being able to adapt to changes in the corporate environment, particularly in the always evolving health industry. The study utilized a quantitative research approach and included 201 participants who were chosen by purposive sampling. The research instrument assessed three primary variables: high-performance human resource management techniques, transformational leadership, and readiness for change. The results of the Structural Equation Model (SEM) research validate that the implementation of high-performance HRM practices and the presence of transformational leadership have a substantial influence on the level of preparedness for change. Research supports the significance of allocating resources towards staff training and development, as well as cultivating effective leadership, in order to enhance employee preparedness for organizational change. The managerial implications of this research underscore the need for organizations to allocate resources for employee development and strengthen leadership that supports change. In this way, organizations can increase their adaptability in facing change and achieve optimal performance overall